2017
DOI: 10.1074/jbc.m116.725614
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Design of Cyclically Permuted HIV-1 gp120 Trimers That Elicit Neutralizing Antibodies

Abstract: A major goal for HIV-1 vaccine development is an ability to elicit strong and durable broadly neutralizing antibody (bNAb) responses. The trimeric envelope glycoprotein (Env) spikes on HIV-1 are known to contain multiple epitopes that are susceptible to bNAbs isolated from infected individuals. Nonetheless, all trimeric and monomeric Env immunogens designed to date have failed to elicit such antibodies. We report the structure-guided design of HIV-1 cyclically permuted gp120 that forms homogeneous, stable trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…By comparing all the groups boosted with monomeric gp120 protein, the OD priming immunogens can be arranged in increasing order of their ability to induce anti-gp120 titers (week 22) as follows: ⌬BS-OD EC Ͻ OD EC Ͻ OD EC C1 Ͻ OD EC Consensus Ͻ OD EC C2 Ͻ OD EC CycV4. Similarly, a comparison of week 22 anti-gp120 titers for the three groups primed with ⌬BS-OD EC but boosted with different Env derivatives indicated that the V1cycP gp120 previously designed by us (30,35,36) provides the best boost for inducing high anti-gp120 titers. In summary, the ELISA results indicated that the OD EC CycV4 and OD EC C2 are the best primes for eliciting sera with high anti-gp120 titers.…”
Section: Design Of Hiv-1 Outer-domain Immunogensmentioning
confidence: 90%
See 1 more Smart Citation
“…By comparing all the groups boosted with monomeric gp120 protein, the OD priming immunogens can be arranged in increasing order of their ability to induce anti-gp120 titers (week 22) as follows: ⌬BS-OD EC Ͻ OD EC Ͻ OD EC C1 Ͻ OD EC Consensus Ͻ OD EC C2 Ͻ OD EC CycV4. Similarly, a comparison of week 22 anti-gp120 titers for the three groups primed with ⌬BS-OD EC but boosted with different Env derivatives indicated that the V1cycP gp120 previously designed by us (30,35,36) provides the best boost for inducing high anti-gp120 titers. In summary, the ELISA results indicated that the OD EC CycV4 and OD EC C2 are the best primes for eliciting sera with high anti-gp120 titers.…”
Section: Design Of Hiv-1 Outer-domain Immunogensmentioning
confidence: 90%
“…V1cycP gp120 molecule is a trimeric cyclic permutant of gp120, made by introducing new N and C termini at the V1 loop (at amino acids 144 -142) while connecting the original N and C termini with a short linker. A human cartilage matrix protein trimerization domain was also added at the newly created N and C termini to generate this cyclically permuted trimeric gp120 variant (human cartilage matrix protein(144 -142) V1cyc-JRCSF gp120), hereafter referred to as V1cycP gp120 (30,35). All four rabbits in group 1 showed undetectable gp120-specific titers after two primes with OD EC protein (at weeks 0 and 4).…”
Section: Design Of Hiv-1 Outer-domain Immunogensmentioning
confidence: 99%
“…We recently described the design and immunogenicity of a novel trimeric gp120 immunogen in guinea pigs ( 19 ). This immunogen, hCMP-v1-cyc-gp120 (referred to as cycP-gp120 here), is based on a cyclically permuted gp120 in which a de novo N terminus is generated within the V1 loop region with the native N and C termini joined via an amino acid linker chain ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently described the design and immunogenicity of a novel trimeric gp120 immunogen in guinea pigs ( 19 ). This immunogen, hCMP-v1-cyc-gp120 (referred to as cycP-gp120 here), is based on a cyclically permuted gp120 in which a de novo N terminus is generated within the V1 loop region with the native N and C termini joined via an amino acid linker chain ( 19 ). To induce a trimeric complex, the human matrix cartilage protein (hCMP) coiled-coil trimerization domain was fused to the de novo N termini, resulting in a stabilized, disulfide bond-linked trimeric gp120 ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The NAB059 elite neutralizer exhibited extraordinarily high titers against a panel of Tier-3 pseudoviruses (26,27), which are the hardest to neutralize. Epitope mapping was also carried out using sera from guinea pigs immunized with an HIV-1 candidate vaccine, a trimeric cyclic permutant (CycP) of gp120 (28) which elicited Tier-2 neutralization activity against a global panel of HIV-1 isolates (29).…”
Section: Polyclonal Epitope Specificity Mapping Using Excyslibmentioning
confidence: 99%